1986
DOI: 10.1002/hep.1840060533
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cancer

Abstract: In recent years, evidence has accumulated of an increased incidence of hepatocellular carcinoma and other cancers of the alimentary tract in the alcoholic (1-3). The thrust of this paper will be to review only briefly the well-known epidemiologic evidence and to discuss in more depth possible mechanisms whereby alcohol abuse may promote the development of cancer.Clinically, an association between heavy drinking and certain types of cancer has been observed for many years. In 1964, the World Health Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
5

Year Published

1987
1987
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(53 citation statements)
references
References 173 publications
(88 reference statements)
0
47
1
5
Order By: Relevance
“…In addition to the possibility discussed above, EtOH has been shown to cause a wide variety of other effects that have the potential to alter steps in gastric carcinogenesis (Lieber et al, 1979). However, in the present work, we found that prolonged i.p.…”
Section: Discussioncontrasting
confidence: 68%
“…In addition to the possibility discussed above, EtOH has been shown to cause a wide variety of other effects that have the potential to alter steps in gastric carcinogenesis (Lieber et al, 1979). However, in the present work, we found that prolonged i.p.…”
Section: Discussioncontrasting
confidence: 68%
“…Subsequently, all of these mice developed chronic hepatitis and HCC. 101 The pathogenetic importance of immune-mediated hepatocellular injury in hepatocarcinogenesis in this study is strengthened by the fact that hepatocellular carcinoma occurs in the context of necrosis, inflammation and regeneration (cirrhosis) in several human liver diseases other than hepatitis B, including chronic hepatitis C, 102 alcoholism, 103 hemochromatosis, 104 glycogen storage disease, 105 ␣-1-antitrypsin deficiency, 106,107 and primary biliary cirrhosis. 108 Irrespective of etiology or pathogenesis, therefore, it would appear that chronic liver cell injury is a premalignant condition that initiates a cascade of events characterized by increased rates of cellular DNA synthesis and production of endogenous mutagens coupled with compromised cellular detoxification and repair functions.…”
Section: Immune Pathogenesis Of Hepatocellular Carcinomamentioning
confidence: 75%
“…Therefore, although the increase in hepatocyte proliferation in response to a combination of EtOH and undernutrition reported in the present study may prevent an increase in severity of steatohepatitis, undernutrition in alcoholics may significantly increase the long-term risk of liver cancer. There are little data in the literature that examine undernutrition as a predisposing component of liver cancer development after chronic alcohol consumption; however, epidemiological data have suggested that poor nutritional status is an important risk factor for esophageal cancer in alcoholics (27). Hepatocytes are normally highly differentiated, metabolically active cells existing in the resting G o state.…”
Section: Discussionmentioning
confidence: 99%